Connecting The Dots: The Impact Of Subclinical Hypothyroidism On Female Subfertility And Obesity - Naila Ashfaq; Warda Hussain; Mugheera Hussain; Neelam Saba; Asma Muddasir; Jawairiah Liaqat (Journal of Rawalpindi Medical College)
Objective: To find the frequency of subclinical hypothyroidism in females with subfertility